Impact of Coastal Squeeze Induced by Erosion and Land Reclamation on Salt Marsh Wetlands - Guangzhi Zhang; Jiali Gu; Hao Hu; Maoming Sun; Jie Shao; Weiliang Dong; Liang Liang; Jian Zeng (Journal of Marine Science and Engineering)
Salt marshes are declining due to the dual pressures of coastal erosion and land reclamation. However, there remains a lack of quantitative analysis regarding this reduction process and its driving mechanisms. This study examines the dynamics and influencing factors of salt marsh vegetation along the eroding coastline of Sheyang County, Jiangsu Province, China, between 1985 and 2020, using remote sensing to analyze changes in artificial coastlines, water boundaries, vegetation front edge, and its topography. Our results showed an extensive seaward movement of artificial coastlines due to reclamation, coupled with severe reductions in salt marsh area and width. Coastal erosion further caused a 10.5% decline in vegetation elevation and a 46.7% increase in slope steepness, amplifying vulnerability to wave action. Native species were largely replaced by Spartina alterniflora, reducing ecological diversity. Currently, human pressure on the landward side has been alleviated; thus, addressing coastal erosion is vital to preventing the further loss of salt marshes. Sediment retention engineering and native vegetation restoration efforts can gradually facilitate the recovery of salt marshes. This study provided critical insights for sustainable coastal management under bidirectional pressures.